Inside Back Cover: Analytical Description of NMR Relaxation Highlights Correlated Dynamics in Intrinsically Disordered Proteins (Angew. Chem. Int. Ed. 45/2017). Issue 45 (17th October 2017) - Salvi, Nicola; Abyzov, Anton; Blackledge, Martin
Abstract : The potential energy landscapes of intrinsically disordered proteins are remarkably flat compared their folded counterparts, making their functional modes difficult to study. In their Communication onpage 14020, M. Blackledge and co‐workers use a combination of high‐resolution NMR spectroscopy and advanced molecular dynamics simulation to investigate the extent of functionally important correlated motions in this essential class of proteins.